Ḵẖut̤bāt-i Mushrān : Shahīd-i Adab Janāb Panḍit Sundar Narāʼīn ṣāḥib Mushrān Faruḵẖ̲ābādī ke Ḵẖut̤boṉ aur taqrīroṉ kā majmūʻah - Mushrān, Sundar Narā̄ʼin, d. 1937 (SAMP early 20th-century Indian books project, 1942)
Chiefly on Urdu literature.